THE DEVELOPMENT OF DIGITAL COMPETENCE IN HIGHER EDUCATION - Амантурлина, Гулмира (Вестник ЗКУ, 2024)
Abstract. The digital transformation of education has fundamentally changed the way students learn and learn in higher education. Building students’ digital competencies is essential to preparing them for the rapidly changing technological landscape. This article presents a comprehensive framework for developing student competence in the context of digitalization of education. Purpose of the study: to develop effective pedagogical strategies and methods for developing digital competence of part-time students. The developed methodology integrates traditional and digital teaching methods. The methodology developed as a result of the author’s research is intended to create a digital ecosystem of higher education.